Study on the Dispersion Characteristics of Thermal Oil Based Nanofluids Using Different Techniques - Lim , Susin (IRC, 2016)
Throughout years of studies by researchers on nanofluids, it is proven that by adding small quantity of nanoparticles into the fluid can lead to increment in fluid thermal conductivity. This discovery benefits the most especially for organic fluids such as thermal oil which having limited thermal conductivity. However, the stability of nanoparticles in the fluid have been one of the main issues that researcher are concerning with. The instability of nanoparticles might cause sedimentation due to the agglomeration of nanoparticles. Therefore, enhancement of nanofluids stability has been the main focus to improve the effectiveness of nanofluids applications. Various methods has been used to study the dispersion behavior of nanofluids such as ultrasonication mixing technique, calcination of nanoparticles and nanoparticles surface modifications.